Pelayanan Charis Mission House Untuk Anak-Anak Di Danau Sentani Papua - Siregar, Roselin; Paulus, Yanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Wira Wacana Sumba, 2023)
The condition of the children in the Lake Sentani area is quite aprehensive. Therefore, the Isa Almasih Pegangsaan Church through the Charis Mission House is moved to serve the children there. The research method used is descriptive qualitative research method which is a study to obtain descriptive data in the form of words and pictures. By serving children through calistung (reading, writing and arithmetic), counseling and spirituality, it is hoped that children in the Sentani Lake area can be fluent in calistung and have the character of Christ. In other words, by blessing children means preparing a good future leader for a nation or country.